Teachers' Challenges in Implementing Deep Learning Assessment in Indonesian Language Instruction at YLPI Perhentian Marpoyan Junior High School, Pekanbaru - Zikry Jawilovia; Muhammad Mukhlis (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study was motivated by the persistence of various challenges in implementing deep learning assessment in Indonesian language learning within the Merdeka Curriculum at the junior high school level. Assessment in the Merdeka Curriculum emphasizes not only learning outcomes but also diagnostic, formative, and summative assessments conducted continuously throughout the learning process. However, in practice, teachers still encounter various obstacles in the planning, implementation, and follow-up stages of assessment. This study aimed to identify and describe the problems faced by teachers in implementing deep learning assessment in Indonesian language learning at SMP YLPI Perhentian Marpoyan Pekanbaru. This research employed a qualitative approach using a case study method. Data were collected through questionnaires and in-depth interviews with Indonesian language teachers at SMP YLPI Perhentian Marpoyan Pekanbaru. Data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and persistent observation. The findings revealed that teachers experienced several challenges in implementing learning assessments. In the planning stage, teachers faced difficulties in time allocation, developing assessment instruments, and determining assessment rubrics and learning achievement criteria. During implementation, large class sizes and limited instructional time hindered teachers from conducting observations, providing feedback, and implementing authentic assessments effectively. In the follow-up stage, teachers encountered difficulties in analyzing assessment results, conducting remedial and enrichment programs, and establishing coordination with parents and other teachers regarding students’ learning outcomes. The study concludes that the implementation of deep learning assessment in Indonesian language learning at SMP YLPI Perhentian Marpoyan Pekanbaru has not been fully optimized due to constraints related to time management, administrative demands, classroom conditions, and limited training and collaborative support. Therefore, strengthening assessment training programs, enhancing school support, and promoting collaboration among teachers are necessary to improve the effectiveness of assessment implementation in the Merdeka Curriculum and better accommodate students’ learning needs.